Kualitas Audit Teknologi Informasi dan Faktor-Faktor yang Mempengaruhinya - Nugroho, Wirawan Arief; Santosa, Paulus Insap; Fauziati, Silmi (Jurusan Teknik Elektro Universitas Negeri Semarang, 2019)
This study aims to determine what factors can affect the Quality of Information Technology Audit. In this paper will describe various studies related to IT Audit, Role of IT Audit, IT Audit Report content and IT Audit Quality. The results are known what factors can affect the Quality of IT Audit and the implications for knowing these factors